Children's Rights Conflict with the Law in the Time of the COVID-19 Pandemic - Riduansyah; Risdalina; Sriono; M, Indra Kumalasari; Siregar, Muhammad Yusuf (International Journal of Criminology and Sociology, 2021)
Children are individuals who are less than 18 years old. Children both in the constitution of the Republic of Indonesia and internationally have the right to be protected. This scientific work aims to analyze the rights of children who are in conflict with the law during the covid 19 pandemic, do children who are in conflict with the law during the covid 19 pandemic get special rights? The method used to obtain data in this scientific work is using the empirical juridical method with primary data obtained directly. Based on the results of the analysis conducted, the rights of children who are in conflict with the law during the COVID-19 pandemic in Indonesia get special rights or get special treatment. The rights of children given are the right to survival (survival rights), the right to grow and develop (development rights), the right to obtain protection (protection rights), the right to participate (participation rights). Giving health rights to children in conflict, and resolving legal conflicts by prioritizing the diversion process, namely the transfer of the settlement of children's cases from the criminal justice process to processes outside criminal justice. There are obstacles or obstacles in handling children who are in conflict with the law, namely in general the detention rooms for children in Indonesia are not adequate, even some areas do not have special detention rooms for children and special investigators for children. and resolve legal conflicts by prioritizing the diversion process, namely the transfer of the settlement of children's cases from the criminal justice process to processes outside of criminal justice. There are obstacles or obstacles in handling children who are in conflict with the law, namely in general the detention rooms for children in Indonesia are not adequate, even some areas do not have special detention rooms for children and special investigators for children. and resolve legal conflicts by prioritizing the diversion process, namely the transfer of the settlement of children's cases from the criminal justice process to processes outside of criminal justice. There are obstacles or obstacles in handling children who are in conflict with the law, namely in general the detention rooms for children in Indonesia are not adequate, even some areas do not have special detention rooms for children and special investigators for children.